Fears and Perception of the Impact of COVID-19 on Patients With Lung Cancer: A Mono-Institutional Survey - Catania, Chiara; Spitaleri, Gianluca; Del Signore, Ester; Attili, Ilaria; Radice, Davide; Stati, Valeria; Gianoncelli, Letizia; Morganti, Stefania; de Marinis, Filippo (Frontiers in Oncology, 2020)
In February 2020, Italy became one of the first countries to be plagued by the SARS-CoV-2 pandemic, COVID-19. In March 2020, the Italian government decreed a lockdown for the whole country, which overturned communication systems, hospital organization, and access to patients and their relatives and carers. This issue had a particular regard for cancer patients. Our Thoracic Oncology Division therefore reorganized patient access in order to reduce the risk of contagion and, at the same time, encourage the continuation of treatment. Our staff contacted all patients to inform them of any changes in treatment planning, check that they were taking safety measures, and ascertain their feelings and whether they had any COVID-19 symptoms. To better understand patients’ fears and expectations of during the pandemic period, we created a nine-question interview, administered from April to May 2020 to 156 patients with lung cancer. Patients were classified by age, sex, comorbidity, disease stage, prior treatment, and treatment type. The survey showed that during the pandemic period some patients experienced fear of COVID-19, in particular: women (55% vs. 33%), patients with comorbidities (24% vs. 9%), and patients who had already received prior insult (radiotherapy or surgery) on the lung (30% vs. 11%). In addition, the patients who received oral treatment at home or for whom intravenous treatment was delayed, experienced a sense of relief (90% and 72% respectively). However, only 21% of the patients were more afraid of COVID-19 than of their cancer, in particular patients with long-term (> 12 months) vs. short-term cancer diagnosis (28% vs. 12.5%, respectively). Furthermore, the quarantine period or even just the lockdown period alone, worsened the quality of life of some patients (40%), especially those in oral treatment (47%). Our data demonstrate how lung cancer patients are more afraid of their disease than of a world pandemic. Also this interview indirectly highlights the clinician’s major guiding principle in correctly and appropriately managing not just the patient’s expectations of their illness and its treatment, but also and especially of the patient’s fears.